2022
DOI: 10.55675/sjms.v1i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Combined Internal Iliac Artery Ligation, Transverse B-Lynch Suture and Intrauterine Balloon to Control Bleeding from Placenta Accreta during Caesarean Delivery

Abstract: Introduction and aim: Placenta praevia and accreta are associated with high morbidity and mortality. Bleeding is the sole etiology of both morbidity and mortality. Thus, anti-bleeding measures are mandatory and research continues to search for ideal prophylactic measure. This work was designed to assess the efficacy of bilateral internal iliac artery ligation followed by Transverse B-Lynch compression suturing and intrauterine balloon tamponade as a conservative methods to control placental site bleeding due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…IIA ligation appears to be a safe procedure that does not impair subsequent fertility and pregnancy outcomes even in combination with other fertility procedures of the uterus (Bakri balloon and B-Lynch suture [ 73 , 74 , 75 , 76 ]. Nizard et al [ 10 ] reported a series of pregnancies following IIA ligation, with normal pregnancy outcomes and no observed infertility among their population.…”
Section: Fertility and Pregnancy Outcomes Following Iia Ligationmentioning
confidence: 99%
“…IIA ligation appears to be a safe procedure that does not impair subsequent fertility and pregnancy outcomes even in combination with other fertility procedures of the uterus (Bakri balloon and B-Lynch suture [ 73 , 74 , 75 , 76 ]. Nizard et al [ 10 ] reported a series of pregnancies following IIA ligation, with normal pregnancy outcomes and no observed infertility among their population.…”
Section: Fertility and Pregnancy Outcomes Following Iia Ligationmentioning
confidence: 99%